Pengaruh Kepuasan, Motivasi Kerja, Dan Komitmen Organisasional Terhadap Kinerja Karyawan Pada PT. Bank Mandiri (Persero), Tbk Area Imam Bonjol Medan - Neni Triastuti; Agnita Yolanda; Eka Wulandari Surbakti; Fahmi Sulaiman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Bank Mandiri (Persero), Tbk Area Imam Bonjol Medan, there has been a decline in employee performance for the last 3 (three) years. Based on the background of the problems described above and to obtain clarity on the issues to be discussed, the authors identify problems, namely (a) Employee Performance which has decreased from the last 3 years. (b) The company's lack of commitment to improve company performance. (c) Some employees do not have a strong motivation to get awards or achievements. (d) Some employees feel dissatisfied with their work and with the salary they receive. Job satisfaction is an emotional attitude that is pleasant and loves his job which is reflected by work morale, discipline and performance. Performance is the result of work that has a strong relationship with the company's strategic objectives, customer satisfaction, and contributes to the economy. Performance is also the result of work and how to get the results of the work. organizational commitment as a psychological state that characterizes the employee's relationship with the organization or its implications that affect whether employees will remain in the company or not, which is identified in three components, namely affective, continuous and normative commitment. Motivation is a behavioral activity that works in an effort to meet desired needs. The purpose of this study was to determine the effect of satisfaction, organizational commitment and work motivation on the performance of employees of PT. Bank Mandiri (Persero), Tbk Area Imam Bonjol Medan. From the results of data processing, obtained a significance value of 0.000 which is smaller than 0.05. From this analysis, Ho is rejected, meaning that there are simultaneously independent variables affecting the dependent variable. To improve employee performance of PT. Bank Mandiri (Persero) Tbk Area Imam Bonjol Medan, it must increase job satisfaction, work motivation and organizational commitment.